Prevalence and determinants of postnatal depression in a tertiary care teaching institute in Kerala, India - T., Heera Shenoy; K., Remash; T., Sheela Shenoy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Pregnancy and childbirth produce a variety of physiological, psychological and social consequences. Attitudes toward pregnancy and childbirth vary from culture to culture. Prevalence estimates range from 13 to 19% in resource-rich settings and 11 to 42% in resource- limited settings PND has a significant impact on the mother, the family, her partner and mother-infant interaction. This research aims to aid the early diagnosis of postnatal depression and the socio-demographic, obstetric, family dynamics, neonatal characteristics and psychiatric determinants of depression using EPDS among postnatal women in a tertiary hospital in Kerala state, India. Methods: 119 women between 2 to 6 weeks of postpartum period were subjected to a pre-tested pre-structured standard questionnaire. Diagnosis of depression was made using the Edinburgh postnatal depression scale. Possible depression is values >13 or more are invariably associated with depression. Results: Young age at marriage (p-value 0.022), love marriage (p-value 0.040) and low social support inadequate relationship with the in-laws was signiﬁcantly associated with PND (p-0.003). Low birth weight was a significant determinant of PND (p-value-0.018). Gender of the new-born, fear and preference towards any particular gender and order of female child in multiparous woman had no association in determining postnatal depression. Childcare stress (p-value-0.011), psychiatry history in family and personal history of depression and mothers with low self-esteem (p-value-0.001) had odds of developing postnatal depression in the study. Conclusions: Early screening of the women and counselling of women and their family will reduce the maternal morbidity and adverse child outcomes.